The Effect of Perceived Price Fairness on Customers Loyalty Mediated by Customers Satisfaction and Perceived Switching Cost - Alonjang, Daisy Ngueban (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The aim of this research is to develop a conceptual background that examines how perceived price fairness affects customer loyalty, with the mediating impact of two variables: customer satisfaction and customer loyalty. Perceived price fairness refers to the judgement customers have of the prices of a good or service being, just, satisfactory and rational. Generally, the customer’s judgment of price fairness impacts their level of satisfaction and loyalty behavior. In addition, perceived switching costs greatly impact customers willingness to maintain a relationship with the business. This study implemented the deductive approach using a sample population of 381student customers of markets/supermarkets in North Cyprus. Quantitative data has been obtained through the use of questionnaires and the above mentioned relationships are analyzed using SPSS statistical software. Results show that the impact of perceived price fairness on customer loyalty is significantly influenced by the levels of customer satisfaction and perceived switching costs. When prices are perceived as unfair, loyalty may still persist if a customer enjoys satisfaction or has high perceived switching cost for shopping from alternative markets. Keywords: perceived price fairness, customer satisfaction, customer loyalty, perceived switching cost, supermarkets in North Cyprus.

ÖZ: Bu araştırmanın amacı fiyat adalet algısının müşteri sadakatini nasıl etkilediğini incelemek ve bu etkiye müşteri memnuniyeti ile algılanan değiştirme maliyetlerinin ne kadar aracılık etkisini yapmakta olduğunu görmektir. Fiyat adalet algısı, müşterilerin bir mal veya hizmetin fiyatlarının tarafsız, tatmin edici ve rasyonel olduğuna karar vermesini ifade eder. Genel olarak, müşterinin fiyat adaleti değerlendirmesi, memnuniyet seviyesine ve sadakat davranışına etki eder. Ek olarak, algılanan değiştirme maliyetleri, müşterilerin şu anki işletme yerine alternatif olarak diğer rakip işletemelere gitmelerinin kendilerine getireceği ilave maliyetleri kapsar. Bu maliyetler de sadakate olan etkilere aracılık etkisi yapabilir. Bu çalışma, Kuzey Kıbrıs'taki 381 müşteri / süpermarket müşterisinin örnek nüfusu kullanılarak tümdengelim yaklaşımını uyguladı. Anketler kullanılarak kantitatif veriler elde edilmiş ve yukarıda belirtilen ilişkiler SPSS istatistik yazılımı kullanılarak analiz edilmiştir. Analiz sonuçlarına göre, fiyat adaleti algısının müşteri sadakatine olan etkisi yüksektir ve bu etkiye hem müşteri memnuniyeti hem de değiştirme maliyeti algısı faktörleri önemli derecede aracılık etkisi yapmaktadır. Bu durumda, fiyatların adaletsiz olduğunu düşünen müşteriler, memnuniyet seviyelerinin yüksek olması veya algıladıkları değiştirme maliyetlerininin yüksek olması halinde sadık müşteri olarak kalmaya devam edebilirler. Anahtar Kelimeler: Fiyat Adaleti Algısı, Müşteri Memnuniyeti, Müşteri Sadakati, Değiştirme Maliyeti Algısı, Kuzey Kıbrıs'taki süpermarketler.
Master of Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2019. Supervisor: Assist. Prof. Dr. Mehmet İslamoğlu.
Keywords: Business Administration; Customer loyalty--Consumers' preferences; Consumer satisfaction--Brand preferences--marketing research--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Consumer attitudes, preferences, reactions--Cyprus, North; Perceived price fairness; customer satisfaction; customer loyalty; perceived switching cost; supermarkets in North Cyprus